Effect of Treatment Delay on Survival in Patients With Cervical Cancer: A Historical Cohort Study. Issue 7 (1st September 2014) - Perri, Tamar; Issakov, Gal; Ben-Baruch, Gilad; Felder, Shira; Beiner, Mario E.; Helpman, Limor; Hogen, Liat; Jakobson-Setton, Ariella; Korach, Jacob
Abstract : Objective: The objective of this study was to evaluate the effect of treatment delay on prognosis in patients with cervical cancer. Methods: The study group of this historic cohort study comprised 321 patients newly diagnosed with cervical cancer between 1999 and 2010. Time from diagnosis to treatment was analyzed both as a continuous variable and as a categorical variable in 3 groups that differed in waiting time between diagnosis and treatment initiation: 30 days or less (group 1, n = 134), 30 to 45 days (group 2, n = 86), and more than 45 days (group 3, n = 101). Associations between waiting time group, patients' characteristics, and disease outcome were investigated using t tests, analyses of variance and Cox regression analyses, Kaplan-Meier survival analysis, and log-rank (Mantel-Cox) tests. Results: Time from diagnosis to treatment initiation, when analyzed as a continuous variable, was not a significant factor in survival. There were no between-group differences in age, smoking rate, marital status, gravidity, parity, tumor histology, or lymph node involvement. Early-stage disease and small tumor diameter were diagnosed most frequently in group 3. However, there was no significant between-group difference in 3-year survival rates (74.6%, 82.2%, and 80.8% in groups 1, 2, and 3, respectively; P = 0.38). On multivariate analysis, only stage, histology, and lymph node involvement were significant prognostic factors for survival. Before starting treatment, 28 patients underwent ovarian preservation procedures. Conclusions: Longer waiting time from diagnosis to treatment was not associated with worse survival. Our findings imply that if patients desire fertility or ovarian preservation procedures before starting treatment, it is acceptable to allow time for them.